Website Creation as A Promotional Media Using Wordpress at Swiss Holiday Tour and Travel Malang - Witantri Kusumastuti; Tri Ramadani Arjo; Tri Istining Wardani (INDO PUBLISHING, 2026)
This research is driven by the rapid development of digital technology, especially the internet, which is transforming the marketing landscape. Swiss Holiday Tour and Travel Malang, which still relies on conventional promotions and inconsistent social media, faces challenges in expanding its market reach and building a professional image. Therefore, developing a website as an efficient promotional tool is a strategic solution. The main objective of this research is to develop a website as a promotional medium for Swiss Holiday Tour and Travel Malang using Wordpress. Additionally, this study aims to evaluate the website's quality based on user perception using the WebQual 4.0 method, as well as measure its effectiveness as a promotional tool. By achieving these objectives, it's hoped that Swiss Holiday Tour and Travel will have an informative, attractive digital platform capable of stimulating purchase interest and customer loyalty. This research uses an action research method with research stages including planning, action, observation, and reflection. Data collection was carried out through interviews, observations, documentation, and questionnaires. The respondents in this study were 16 people, with details of 2 marketing experts, 2 design experts, 1 owner, and 10 customers. The research findings indicate that the developed website is highly effective as a promotional medium, with a WebQual score reaching 87% on an